Study on the association between TGF-β1 and liver fibrosis in patients with hepatic cystic echinococcosis - Tian, Fengming (Exp Ther Med, 2020)
The present study aimed to determine the role of the cytokine transforming growth factor-β1 (TGF-β1) in liver fibrosis among patients with hepatic cystic echinococcosis (hepatic CE). Hepatic tissue specimens and serum samples from 30 patients with hepatic CE were collected and TGF-β1 levels were compared between the two groups. The degree of liver fibrosis was assessed by Masson staining. The expression levels of cytokine TGF-β1 in liver tissue and serum were detected by immunohistochemistry and ELISA, respectively. Masson staining of liver lesion tissue in patients with hepatic CE indicated different degrees of fibrosis in the liver and the World Health Organization classification was positively correlated with the severity of liver fibrosis (P<0.05). In addition, the expression of cytokine TGF-β1 was higher in liver lesion tissue specimens compared with that in the adjacent control samples (P<0.05). At the same time, cytokine TGF-β1 in serum specimens of patients was higher than that in the healthy control group (P<0.05). In conclusion, the expression of TGF-β1 is upregulated in patients with hepatic CE, which was closely associated to liver fibrosis.